2000
DOI: 10.1108/02683940010379341
|View full text |Cite
|
Sign up to set email alerts
|

Work and family expectations of the future managers and professionals of Canada and China

Abstract: This study investigates the work‐family expectations of the next generation Canadian and Chinese managers and professionals. Three hundred and seventy‐four Canadian and Chinese business students of both sexes were surveyed about their expectations about their own and their spouse’s/partner’s future occupational and family roles. The data revealed that Chinese of both sexes attached greater value to their occupational role and would commit more time to it than Canadians. They also anticipated less difficulty ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…Anticipated work-family conflict was a unidimensional scale indicating that South African students do not distinguish between the family to the work and work to family directionality of AWFC (c.f., Cinamon, 2006;Gutek et al, 1991), which is consistent with many other applications of AWFC (Weer et al, 2006;O'Shea & Kirrane, 2008;Bu & McKeen, 2000;Livingston Burley & Springer., 1996). Similarly, self-efficacy to manage future work-family conflict (SE-FWFC) was a unidimensional scale (Hennessy 7 Lent, 2008).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Anticipated work-family conflict was a unidimensional scale indicating that South African students do not distinguish between the family to the work and work to family directionality of AWFC (c.f., Cinamon, 2006;Gutek et al, 1991), which is consistent with many other applications of AWFC (Weer et al, 2006;O'Shea & Kirrane, 2008;Bu & McKeen, 2000;Livingston Burley & Springer., 1996). Similarly, self-efficacy to manage future work-family conflict (SE-FWFC) was a unidimensional scale (Hennessy 7 Lent, 2008).…”
Section: Resultssupporting
confidence: 68%
“…There was no significant difference between black and white students on AWFC. In South Africa, race may be considered a crude proxy for cultural and socialisation differences not investigated in this study; it was included because cultural differences in experiencing work-family conflict have been found in previous research (Bu & McKeen, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Chinese women take on substantially more household responsibilities and tasks than their husbands. Bu et al reported that Chinese female employees spent an average of 3.7 h per day on housework compared to 2.2 h per day for male employees 14) . In a study investigating the work-family expectations of business students in China, 57.8% of Chinese men expected the wife would do a disproportional larger share of housework 14) .…”
mentioning
confidence: 99%
“…Bu et al reported that Chinese female employees spent an average of 3.7 h per day on housework compared to 2.2 h per day for male employees 14) . In a study investigating the work-family expectations of business students in China, 57.8% of Chinese men expected the wife would do a disproportional larger share of housework 14) . Therefore, we examined the association between WIF/FIW and burnout separately among male and female doctors to investigate the role of gender as a moderator of the posited relations.…”
mentioning
confidence: 99%
“…Women are assumed to civilize men and to contribute intrinsic skills to organizational communication that men seemingly lack. This added value is outweighed, however, by women's supposed inability to be like managerial men who work long hours and who have delegated caregiving responsibilities to others (see also Bu and McKeen 2000, Lyon and Woodward 2004, Ford and Collinson 2011. The managers in this study assumed the time obligations of managerial positions are fixed and that women with children choose not to engage in the normalized long hours.…”
Section: Constructing Women and Minoritiesmentioning
confidence: 99%